Implementation of the San Remo Manual as a Strategy for the Rule of War in the Indonesian Marine Territory - KAMARULAH, Rizki Pratama; PRAKOSO, Lukman Yudho (Protection: Journal Of Land And Environmental Law, 2023)
In 1994, a regulation on sea warfare was made, which could be used by countries conducting sea wars. This regulation is called the San Remo Manual, with changes to make various adjustments related to the conduct of war at sea. Indonesia is in an important strategic area both in the sea and air zones, this makes Indonesia a strategic area both regionally and globally. The purpose of this research is to provide practical guidelines for countries in applying international law that applies in times of armed conflict at sea and to find out how the law is applied in Indonesia. This study uses a qualitative method. Qualitative research tries to identify various phenomena ideographically. The theory of development and development can be formed empirically through various phenomena or cases studied. the result of this is to become a guideline for countries in conducting wars at sea, armed conflicts at sea, parties involved in the conflict, actions that are permitted and which are not permitted during conflicts, protection of injured ships and people who are injured or captured, as well as actions taken can be taken by countries outside the conflict.